Writing for the green light : how to make your script the one hollywood notices - Kirkpatrick, Scott (Focal Press, 2015)
Tailor your screenplay to sell. Find out what Hollywood script readers, producers, and studio executives want in a screenplay (and why) from someone who's been there. Discover what it takes to begin a lasting career as a screenwriter. Peppered with interviews from established professionals, Writing for the Green Light: How to Make Your Script the One Hollywood Notices gives you a sharp competitive edge by showcasing dozens of everyday events that go on at the studios but are rarely if ever discussed in most screenwriting books. With his behind-the-scenes perspective, Scott Kirkpatrick shows you.